Isothermal drying kinetics of sewage sludge using weathered coal fly ash as adjuvant for agronomic application. Issue 14 (20th June 2021) - Gomes, Luciano A.; Santos, Andreia F.; Lopes, Rui J. A.; Góis, José C.; Quina, Margarida J.
ABSTRACT: This study aims to evaluate the effect of weathered coal fly ash (CFA) as a drying adjuvant of sewage sludge (SS) to produce a soil amendment. The high amount of SS and CFA creates a complex waste management problem in many countries, requiring more research efforts. Towards a circular economy, CFA can be viewed as an anthropogenic inorganic by-product with valuable nutrients (e.g. K), which can be recovered in combination with SS (rich in organic matter, N, and P). Different temperatures (70, 85, 100, 115, and 130 °C) are tested to dry small SS cylinders, without and with 0.15 g CFA g −1 of SSwet basis (wb) . By fitting appropriate models to the experimental drying curves, it is possible to observe an improvement of 1-17% in the diffusion coefficient and 7-19% in the kinetic constants, using CFA. The best drying conditions are achieved with CFA as an adjuvant at 130 °C, where the drying rate is 31.61 gH2 O kg −1 SSwb min −1 . Phytotoxicity and growth assays are performed to evaluate the effect of the produced materials in the soil. The product with SS and CFA shows the potential to improve soil condition due to (i) the organic matter, N, P, and K content, (ii) the lower phytotoxic effect when compared to raw SS; (iii) the soil pH correction. Thus, not only the addition of weathered CFA facilitates the drying of SS but also the final product has benefits to soil conditions. GRAPHICAL ABSTRACT: UF0001